HUBUNGAN GANGGUAN FASE SEKSUAL DENGAN PENGGUNAAN KB HORMONAL PADA AKSEPTOR KB - JANURIWASTI, DIAN EKA; Ningsih, Maulid Kurnia (NHM PRESS, 2021)
The use of contraceptives is one of the efforts in preventing pregnancy. One of the problems that arise due to the use of contraceptives is sexual problems. This can certainly have a hormonal impact on the quality of life of emotional health for a woman. Based on preliminary studies conducted in Polindes Poter Village, Tanah Merah Subdistrict, Bangkalan Regency obtained from 5 DMPA injectable KB acceptors, there were 2 people (40%) who experienced sexual arousal phase disorder, while out of 5 people (60%) who used combination injectable KB, also obtained 3 people who experienced sexual arousal disorder. The purpose of this study is to find out the relationship of sexual phase disorders with the use of KB Hormonal in KB acceptors in Polindes Poter Village, Tanah Merah District. The research uses quantitative design with an analytic approach. The variables in the study were free variables (Independent): Use of Hormonal Birth Control and Dependent Variables: Sexual phase disorders in birth control acceptors.How to collect samples with proportional sampling and data retrieval techniques using questionnaires, data was taken on 64 hormonal birth control acceptors injected DMPA 27 people, injectable combination 24 people, Mini Pill 6 people and Combination Pill 7 people in Polindes Village Poter Tanah Merah Madura and the results were analyzed descriptively and hypothesis test using Rank Spearmen. Analysis of Rank Spearman showed that there was a relationship of sexual phase disorders with the use of KB Hormonal in KB acceptors in Polindes Poter Village Tanah Merah Subdistrict (p-value = 0.015). The results of this study are expected as a development of science regarding sexual phase disorders in hormonal birth control acceptors.